2018
DOI: 10.3329/ajmbr.v3i4.35342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density on the growth rate of gold fish fry reared in hapa

Abstract: Abstract:The present study was conducted to investigate effects of stocking density on growth performances of gold fish (Carassius auratus) in hapas. Experiment was conducted for a month with three treatments where three stocking densities were T 1 (10 fry/hapa), T 2 (15 fry/hapa) andT 3 (20 fry/hapa) each having three replications which were selected randomly. In the present experiment hapa (3ft × 2ft × 2ft) with 1 mm mesh net was used. Gold fish fry having a mean body weight of 0.007 g were used in all treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
6
7
0
Order By: Relevance
“…Only in winter months, sometimes morning fog and heavy dew were observed and in monsoon, occasionally gusty wind prevails in this area (Akther, 2018). The maximum air temperature (27.50±0.70C) in pre-monsoon and water temperature (31.5±0.80C) in monsoon was recorded while minimum air temperature (21.00±1.30C) in post-monsoon and minimum water temperature (23.5±1.50C) in post-monsoon was recorded and similar season wise temperature change observation was conducted by Zafar et al, (2017) and Shajib et al, (2017). Air temperature in the study area was found always higher than water temperature except in a few cases.…”
Section: Discussionsupporting
confidence: 85%
“…Only in winter months, sometimes morning fog and heavy dew were observed and in monsoon, occasionally gusty wind prevails in this area (Akther, 2018). The maximum air temperature (27.50±0.70C) in pre-monsoon and water temperature (31.5±0.80C) in monsoon was recorded while minimum air temperature (21.00±1.30C) in post-monsoon and minimum water temperature (23.5±1.50C) in post-monsoon was recorded and similar season wise temperature change observation was conducted by Zafar et al, (2017) and Shajib et al, (2017). Air temperature in the study area was found always higher than water temperature except in a few cases.…”
Section: Discussionsupporting
confidence: 85%
“…In the experiment water parameters, such as pH, temperature, salinity and DO were varied from 7.7-8.1 28.4-32.7°C, 17.1-19.3 ppt and 7.7-8.3 mg/L respectively which is acceptable range for crab fattening according to Cholik and Hanafi (1992) and showed similarity with Begum et al, (2009). The water quality management is also supported by the study of different researcher (Ali et al, 2016;Shabuj et al, 2016;Shajib et al, 2017;Zafar et al, 2017;Rahman et al, 2018;Akter et al, 2018;Faruk et al, 2018;Biswas et al, 2018;Billah et al, 2019).In the present experiment, 100% survival was obtained for crabs fed with Chicken intestine and Apple snail meat. The other feeds had lower survival rate and it was 90%.…”
Section: Discussionsupporting
confidence: 67%
“…The maximum value was recorded with the T 1 in the fourth months. Samad et al (2021) suggested the temperature in the culture setup were 28.50°C among the treatments while Nahar et al (2021) found temperature fluctuated between 25.01 and 26.13°C; on the other hand Shajib et al (2018) showed the temperature could be ranged between 25.25 and 27.50 °C in hapa set up was found to be suitable for fish growth, as better weight gain and lower FCR were recorded during this period. The amount of dissolved oxygen in water is another key water quality characteristic that fish rely on to survive (Makori et al, 2017).…”
Section: Discussionmentioning
confidence: 97%